(untitled) (Journal of the College of Basic Education, 2023)
The problem of the world that fills the thought of humanity today and touches its reality to the core is the problem of the social system, which is summed up in giving the most sincere answer to the following question: What is the system that is suitable for humanity and makes it happy with it in its social life?It is natural that this problem occupies a dangerous position, and that in its complexity and the diversity of the colors of diligence in resolving it, it is a source of danger to humanity itself. Because the system is included in the calculation of human life and influences its social entity to the core.This problem is evident throughout its long history in the nature of the conflict between private self-interests and general social interests, and God Almighty sent the prophets to convey humanity to advanced stages of awareness and insight into man’s mission in life and to make him understand the goals and objectives of his existence, and to clarify the motives for building life and investing it for him, so that this may be done. Directing it and linking it to God  and the Hereafter, so that bitter conflict between the two contradictory interests is eliminated, and complete harmony is created between them, as that relationship and that link is sufficient to develop the concept of man who is innate on self-love and striving towards his own interests, a development that removes the conflict and ends the problem, had it not been for heaven, it would have been hard Humanity has a history that has terrible colors and harsh images of this problem, more severe than what it went through, and what humanity faces today in terms of human grievances and aggression against his brother, are nothing but multiple images of one problem represented by the deviation of instinct from the message of the pure monotheistic religion represented by true Islam.